2023
DOI: 10.1108/qrfm-02-2022-0028
|View full text |Cite
|
Sign up to set email alerts
|

Application of tawarruq in Islamic banking institutions in Somalia

Abstract: Purpose The purpose of this study is to examine the acceptability of tawarruq in the banking industry in Somalia, focusing on awareness, need, compatibility, relative advantage, behavioral attitude and the role of Shariah scholars. This study is governed by the Theory of Islamic Consumer Behavior. Design/methodology/approach A questionnaire survey was conducted involving 150 customers of Islamic banks in Mogadishu, Somalia. This research adopts a quantitative methodology, using descriptive and survey analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 33 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…Adapting the viewpoints of Saygılı et al (2022) and Raza et al (2019), attitude is the consumers’ attitude toward Islamic banks, in which a customer considers an Islamic bank is profitable and advantageous. Haron and Mohamed Barre (2023) research demonstrated a high correlation between customer views and aspirations to convert to Islam by using Islamic banks. The attitude of Muslim customers toward a product or service acts as an internal predictor that can influence specific intentions and behaviours (Lebdaoui et al , 2022; Pratama et al , 2023; Saygılı et al , 2022), such as adherence to Islamic principles by deciding to become a customer of an Islamic bank (Lebdaoui et al , 2022; Pratama et al , 2023; Mindra et al , 2022).…”
Section: Results and Analysismentioning
confidence: 96%
See 4 more Smart Citations
“…Adapting the viewpoints of Saygılı et al (2022) and Raza et al (2019), attitude is the consumers’ attitude toward Islamic banks, in which a customer considers an Islamic bank is profitable and advantageous. Haron and Mohamed Barre (2023) research demonstrated a high correlation between customer views and aspirations to convert to Islam by using Islamic banks. The attitude of Muslim customers toward a product or service acts as an internal predictor that can influence specific intentions and behaviours (Lebdaoui et al , 2022; Pratama et al , 2023; Saygılı et al , 2022), such as adherence to Islamic principles by deciding to become a customer of an Islamic bank (Lebdaoui et al , 2022; Pratama et al , 2023; Mindra et al , 2022).…”
Section: Results and Analysismentioning
confidence: 96%
“…The previous findings gave a thorough understanding of the concepts and practise of Islamic finance, including a discussion of consumer behaviour in the context of Sharia compliance (Lebdaoui et al , 2022). Other studies shed light on the fundamentals of Islamic finance and the variables that influence customer behaviour in Islamic financial goods and services (Haron and Mohamed Barre, 2023). Several studies have analysed the elements affecting Islamic banking’s profitability, focusing on client behaviour in selecting Islamic banking services (Junaidi et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations